Assessment of the quality of immunization data produced by the national individual registration system in Uruguay, 2006 Evaluación de la calidad de los datos de vacunación generados por el sistema nacional de registro individual en Uruguay, 2006 - Olivier Ronveaux (Revista Panamericana de Salud Pública, 2009)
OBJECTIVE: The nominal registration system of Uruguay's national immunization program (NIP) tracks administered vaccines on a paper form filled out after each vaccination and collated into a national database, thus allowing for individual follow-up. This study performed a comprehensive assessment of the quality of Uruguay's immunization data in November 2006 to evaluate the validity of the information and to confirm the high national immunization coverage reported by the program. METHODS: The research team analyzed the concordance of the operational-level numerators (infant immunization data from 18 public and private vaccination centers in six country departments) with department- and national-level data, and compared the national-level (NIP) infant denominators with other official sources. A standardized questionnaire was used to evaluate system performance at the operational (vaccination center), department, and national level. Rapid house-to-house monitoring was conducted to generate additional coverage estimates. RESULTS: Numerator accuracy throughout the data flow was 100%, and national-level denominators appeared to be exhaustive. Overall system performance was excellent (proper archiving and recording of form data, sufficient supply of forms, timely flow of information, adequate defaulter tracing practices and computer system security). The main weaknesses were the degree of data analysis and feedback to peripheral levels. House-to-house monitoring showed high overall immunization coverage (97%). CONCLUSION: Uruguay's NIP registration system produces remarkably reliable information, ensuring valid measurement of immunization coverage. In addition, by allowing for monitoring of each child's current vaccination status, it facilitates management of interventions designed to reduce vaccination default and thus helps achieve the country's high level of coverage. OBJETIVOS: El sistema de registro nominal del programa nacional de vacunación (PNV) de Uruguay registra las vacunas administradas en un modelo en papel que se llena después de cada vacunación y se introduce en una base de datos nacional, lo que permite el seguimiento individual. En este estudio, realizado en noviembre de 2006, se hizo un análisis integral de la calidad de los datos de vacunación en Uruguay para evaluar la validez de la información y confirmar la alta cobertura nacional de vacunación informada por el programa. MÉTODOS: Se analizó la concordancia de los numeradores operacionales (datos de vacunación infantil de 18 centros de vacunación públicos y privados de seis departamentos del país) con los datos departamentales y nacionales, y se compararon los denominadores del PNV infantil a nivel nacional con los de otras fuentes oficiales. Se empleó un cuestionario estandarizado para evaluar el desempeño del sistema en los niveles operacional (centros de vacunación), departamental y nacional. Se realizó un monitoreo rápido de casa en casa para obtener estimados adicionales de la cobertura. RESULTADOS: La precisión de los numeradores en todo el flujo de datos fue de 100% y los denominadores a nivel nacional al parecer eran exhaustivos. El desempeño general del sistema fue excelente (archivo y registro adecuados de los datos, suministro suficiente de modelos, flujo oportuno de información, práctica adecuada de rastreo de fallas y sistema apropiado de seguridad informática). Las principales debilidades fueron el grado de análisis de los datos y la retroalimentación a las instancias periféricas. El monitoreo de casa en casa mostró una alta cobertura general de vacunación (97%). CONCLUSIONES: El sistema uruguayo de registro del PNV genera una información notablemente confiable, lo que asegura la validez de la medición de la cobertura de vacunación. Además, al permitir el monitoreo del estado de vacunación actual de cada niño, facilita la aplicación y el control de intervenciones diseñadas para reducir las omisiones en la vacunación y ayudar así a alcanzar un alto nivel de cobertura en el país.